1984
DOI: 10.1159/000215083
|View full text |Cite
|
Sign up to set email alerts
|

Low Molecular Weight (LMW) Heparin Derivatives in Experimental Extra-Corporeal Circulation (ECC)

Abstract: Low molecular weight (LMW) heparin has been shown to prevent experimental venous thrombosis. In order to investigate its biological action and its potential use in open heart surgery, we have conducted an experimental study using extracorporeal circulation (ECC) in sheep as an experimental model. 18 sheep were randomly selected to receive either LMW heparin (2 mg/kg), high dose heparin (HD; 160 U/kg), or low dose heparin (LD; 60 U/kg). The HD heparin yielded the same circulating anti-activated factor X (anti-X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Aiach et al [35], reporting on the use of LMWHs in a sheep model of extracorporeal circulation, found that they effectively prevented thrombus formation within the circuit. Hemostatic activation and consumption of fibrinogen, factor V, antithrombin III and platelets were similar in experiments with LMWH and either low-or high-dose UFH.…”
Section: Low Molecular Weight Heparinmentioning
confidence: 99%
“…Aiach et al [35], reporting on the use of LMWHs in a sheep model of extracorporeal circulation, found that they effectively prevented thrombus formation within the circuit. Hemostatic activation and consumption of fibrinogen, factor V, antithrombin III and platelets were similar in experiments with LMWH and either low-or high-dose UFH.…”
Section: Low Molecular Weight Heparinmentioning
confidence: 99%
“…The relation ship between LMW heparin and reduced bleeding may therefore be more related to a diminished effect on platelets than on blood clotting. For example, 2 groups failed to demonstrate a correlation between anti-Xa blood levels or APTT and bleeding compli cations, either in rabbits or in man [15,17], Aiach et al [18] reported their experience with an LMW heparin in sheep during extra corporeal circulation. While LMW heparin was an effective alternative to heparin in car diac surgery, with no post-operative circulat ing activity prolonging the APTT, they were unable to demonstrate a reduced incidence of haemorrhagic complications in their animals.…”
Section: Incidence Of Bleedingmentioning
confidence: 99%
“…1,2,5,11,17,19,20 LMW heparins have been shown to prevent thrombus formation or to reduce thrombus extension in numerous experimental models. 3,6,19 Clinical efficacy in postoperative venous thrombosis prophylaxis has also been demonstrated. 10 The use of LMW heparins in clinical trials needed the development of biologic assays aimed at assessing the in vitro biologic potency of the commercial preparation and monitoring the in vivo biologic effects.…”
mentioning
confidence: 99%